Transcatheter closure of postmyocardial infarction, iatrogenic, and postoperative ventricular septal defects: The Mayo Clinic experience. Issue 7 (29th May 2015) - Egbe, Alexander C.; Poterucha, Joseph T.; Rihal, Charanjit S.; Taggart, Nathaniel W.; Cetta, Frank; Cabalka, Allison K.; Pollak, Peter M.; Reeder, Guy S.; Hagler, Donald J.
Abstract : Objectives: To determine event‐free survival after transcatheter closure of ventricular septal defect (VSD), and to identify predictors of adverse events (AE) in post myocardial infarction VSD (post‐MI VSD) subgroup. Background: There are limited data on mid‐term follow‐up after transcatheter VSD closure. Methods: Retrospective review of 27 cases of transcatheter VSD closure (post‐MI = 18 and non‐ischemic = 9) performed from 1999 to 2013. We defined AE as death, device embolization, hemolysis requiring blood transfusion, heart block and reintervention. Results: In the post‐MI VSD subgroup, mean age and follow‐up was 69 ± 11 and 7.3 ± 7 years, respectively. AE occurred in 8 (44%) patients (death‐3, device embolization‐1, hemolysis‐1, surgical VSD closure‐2, reintervention‐1). Event‐free survival was 56% at 1 month and 5 years, and all AE occurred in the periprocedural period. Cardiogenic shock (HR: 3.21, CI: 1.82–5.41, P = 0.002), and VSD closure in acute phase (HR: 2.14, CI: 1.12–4.31, P = 0.004) were independent predictors of AE. In the non‐ischemic VSD subgroup, mean age and follow‐up was 49 ± 15 and 8.7 ± 8 years, respectively. AE occurred in 3 (33%) patients (late death‐1, surgical VSD closure‐2). For the entire cohort, freedom from death was 89% and 85% at 1 month and 5 years, and event‐free survival was 70% and 61% at 1 month and 5 years. Conclusions: Transcatheter closure of post‐MI VSD carries a moderate risk of periprocedural complications but low event rates afterwards. By comparison, device closure of non‐ischemic VSD has lower periprocedural morbidity but some patients continued to experience AE during follow‐up. © 2015 Wiley Periodicals, Inc.